How breastfeeding affects immunity? - Dawid Piecuch; Weronika Sobota; Katarzyna Zemsta; Przemysław Piskorz; Michał Zwoliński; Edyta Hańczyk; Aleksandra Sędek (Quality in Sport)
Introduction and objective